CRITICAL ANALYSIS ON EFFECTIVE WAYS USED IN TREATING PREGNANCY-INDUCED HYPERTENSION. - 1Reham Fahad Almohamadi, 2Layla KiesAlmatteri, 3Njood Mohammed Almutairi, 4Saud Madi Alotaibi, 5Sabaa MoidhAlanazi, 6Sami Abdullah Alotaibi, 7Abdulaziz AbdulhamidAlanazi, 8Mishal Abdullah Alotibi (Chelonian Research Foundation, 2022)
Pregnancy-induced hypertension (PIH) is a critical issue that influences the health of both the mother and the child during pregnancy. This vital survey investigates compelling medications for pregnancy with high blood weight, counting sedate mediations, way of life changes, and birth control techniques. They coordinated fundamental discoveries from clinical considerations and strategies to assess the viability, security, and results related to diverse medicines. The talk investigates the components of activity, potential benefits, and restrictions of different treatment choices, considering their impacts on maternal blood control, the anticipation of issues, and the healthcare of the baby. Suggestions are advertised to make strides in blood weight control during pregnancy, emphasizing numerous approaches, self-care, and quality care to make strides in maternal and newborn child outcomes.